Elastic beam vibration control with phase-locked loop - Lopes, Guilherme Cano [UNESP]; Bueno, Átila Madureira [UNESP]; Balthazar, José Manoel [UNESP] (ASME International, 2014)
The Phase-Locked Loop (PLL) is a closed-loop control system that synchronizes a local oscillator to an oscillatory incoming signal. The PLL plays important roles in communication, computation and control systems, allowing the correct flow of information by efficiently generating and distributing clock reference signals. PLLs are also applied in motor speed control and in atomic force microscopy. Nevertheless, PLLs are inherently nonlinear devices, and behaviors such as bifurcations and chaos may arise. In this paper, the vibration control of an elastic beam is performed by a PLL control structure. Additionally, different designs for the PLL-beam control system are discussed.